Assessment of hand grip strength in Mexican boxers by training phase - Ramirez Garcia, C. M.; Harasymowicz, J.; Viramontes, J.; Ordenes, I.; Vazquez, F. B. (Archives of Budo, 2010)
Background and Study Aim: Boxing bouts are explosive by nature as they include components of speed and power in order to be effective. If a boxer cannot produce power, his performance will be limited. This was the paramount motivation to perform a study on the evolution of the gripping strength in both hands as an indirect indicator of upper limb strength, since this is a major factor in the medical control of boxing matches.